Gender non-binary adolescents’ somatic and mental health throughout 2020 - Johansson, Catrin; Kullgren, Carina; Bador, Kourosh; Kerekes, Nóra (Frontiers in Psychology, 2022)
Background: Non-binary gender adolescents are particularly vulnerable and more likely to be exposed to several socio-psychological difficulties and disorders. It is vital to discover and act on the vulnerabilities they encounter. The present study aims to describe the somatic and mental health, affect state, frequency of risk behaviors, victimization and negative psychosocial factors, as well as the personality profiles of non-binary adolescents. In this study the concept of gender non-binary is used and captured respondents who selected “neither of these” as their gender from the possible options (female/male/neither of these). Materials and methods: Data was collected between September 2020 and February 2021 in Sweden, Morocco, Serbia, Vietnam, and the USA. The cross-sectional, retrospective study utilized the electronic version of the Mental and Somatic Health without borders (MeSHe) survey. From the over 5000 responses of 15–19-year-old adolescents, 58 respondents identified as being non-binary, and built our study population. Their data was analyzed with descriptive statistic methods. Results: Close to a fourth of adolescents identifying as non-binary reported the existence of at least one somatic disease. The most prevalent somatic disease was allergies. Almost one-third had suffered from pain either often or all the time in the past 12 months. The highest levels of perceived psychological distress were measured using obsessive-compulsive symptoms, depression, and interpersonal sensitivity. The average level of alcohol and drug use during the past 12 months was low. About 40% of non-binary adolescents reported having experienced physical abuse, and half of them experienced psychological abuse at some point in their lives. Seventeen percent reported living with adults with alcohol-use problems. Non-binary adolescents’ personalities were found to be dominated by high scores in Openness, Neuroticism, and Agreeableness. Conclusion: This study presents a detailed biopsychosocial picture of a multinational sample of non-binary adolescents. Our study suggests that awareness and support are required from all fields of society, including family, school, healthcare, and educational institutions, for cis-normative culture to progress toward a greater understanding of and respect for gender diversity.